Adolescent chronic intermittent toluene inhalation dynamically regulates the transcriptome and neuronal methylome within the rat medial prefrontal cortex. (7th July 2020) - Dick, Alec L.W.; Zhao, Qiongyi; Crossin, Rose; Baker‐Andresen, Danay; Li, Xiang; Edson, Janette; Roeh, Simone; Marshall, Victoria; Bredy, Timothy W.; Lawrence, Andrew J.; Duncan, Jhodie R.
Abstract: Inhalants containing the volatile solvent toluene are misused to induce euphoria or intoxication. Inhalant abuse is most common during adolescence and can result in cognitive impairments during an important maturational period. Despite evidence suggesting that epigenetic modifications may underpin the cognitive effects of inhalants, no studies to date have thoroughly investigated toluene‐induced regulation of the transcriptome or discrete epigenetic modifications within the brain. To address this, we investigated effects of adolescent chronic intermittent toluene (CIT) inhalation on gene expression and DNA methylation profiles within the rat medial prefrontal cortex (mPFC), which undergoes maturation throughout adolescence and has been implicated in toluene‐induced cognitive deficits. Employing both RNA‐seq and genome‐wide Methyl CpG Binding Domain (MBD) Ultra‐seq analysis, we demonstrate that adolescent CIT inhalation (10 000 ppm for 1 h/day, 3 days/week for 4 weeks) induces both transient and persistent changes to the transcriptome and DNA methylome within the rat mPFC for at least 2 weeks following toluene exposure. We demonstrate for the first time that adolescent CIT exposure results in dynamic regulation of the mPFC transcriptome likely relating to acute inflammatory responses and persistent deficits in synaptic plasticity. These adaptations may contribute to the cognitive deficits associated with chronic toluene exposure and provide novel molecular targets for preventing long‐term neurophysiological abnormalities following chronic toluene inhalation. Abstract : Inhalant abuse is most common during adolescence and can result in cognitive impairments during an important maturational period. We demonstrate for the first time that chronic adolescent toluene exposure results in dynamic regulation of the transcriptome and DNA methylation profiles in the rat prefrontal cortex. These adaptations may contribute to the long‐term cognitive deficits associated with inhalant abuse and provide novel molecular targets for preventing long‐term neurophysiological abnormalities following chronic toluene inhalation.